PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEBERANIAN DAN PRESTASI BELAJAR - Lip Syafridawati (DIADIK, 2024)
The aims of this study are: (1) To describe the students' courage in the content of mathematics lessons through the application of RME. (2) To describe student learning achievement on the content of mathematics lessons through the application of the RME learning model. (3) To describe the effectiveness of the application of the RME learning model in increasing students' courage and achievement in mathematics lessons in class VI SDN 03 Mukomuko City District. In this study, the Classroom Action Research Model (CAR) was used and continued with Quasi Experimental research. The subjects of this study were students of class VI SDN 03 Mukomuko City District. With class VIc as the CAR class, class VIb as the experimental class, and class VIa as the control class. Data collection techniques used in the study were observation sheets and student test models. Analysis of the data used values are (1) Analysis of Student Courage (2) Analysis of Pre-test and Post-Test, (3) Analysis of Student Achievement Test. Instrument validation and student courage. The conclusions of this research are; (1) The application of the RME learning model can increase students' courage. (2) The application of the RME learning model can improve student achievement in Mathematics in Class VI SDN 03 Mukomuko City in the 2022/2023 academic year and (3) The application of the RME learning model in improving student achievement compared to learning models that do not use the RME model